Development of Voltammetric Method for Citrate Analysis Using Carbon Paste Electrode - NOVI YANTI (NIM 10505087), LUSI
Citrate is electroinactive, therefore citrate determination is not normally conducted using voltammetry method. In this research, a new indirect voltammetry method is developed for citrate analysis. The decrease of Fe(III) reduction current on carbon paste electrode due to complex formation of Fe(III) and citrate was used in the analysis. The decrease of Fe(III) reduction peak is proportional to the concentration of citrate. Two voltammetry techniques, namely, differential pulse voltammetry and squerewave voltammetry was used in this study. Optimum composition carbon paste electrode contained 70% graphite and 30% paraffin. Calibration curve is linear in the range of 0,1 mM to 6 mM of citrate. The accuracy of spike sample analysis was good with percent recovery of 99,24 %-103,89%. However accuracy of citrate analysis of soft drink sample is not as good due to matrix of the sample.